Reasons Associated With Common Contraceptive Methods Used among Women in Qaladze District - Parzhin Abdulla Ibrahim; Sanna Hassan Abdulsahib (Kufa Journal for Nursing Sciences)
Back ground Family planning is the deliberate use of contraception to arrange a couple's desired childbearing plan and number, family planning is the practice of using contraceptives to avoid unplanned pregnancies, have fewer children, and spacing out childbirths. Aim To assess reasons associated with common family planning methods used among women in Qaladze district. Material and method A cross-sectional study was conducted on 180 women of reproductive age 15-49 years old, who were attending in two private gynecology and obstetrical clinics and Qaladze general teaching hospital in Qaladze district. Data collection started on 1 st of June, 2022 and ended in 1st August, 2022.a non-probability purposive sampling used to recruit 180 women who were living in Qaladze district and its surroundings. Special questionnaire constructed for proper data collection based on extensive review of related literature and studies. For data processing and statistical analysis, the statistical program for social science (SPSS, Version 25) was used. This package featured descriptive statistical analysis, such as frequency and percentage to characterize the essential characteristics of the data, as well as figures. Results The mean age of the respondents was (34 ±6.842), most of the respondents (31.1%) fall in the age bracket of (31-36) years, regarding women’s occupational status. Most proportion of the respondents were house wife (73.9%, n=133). In the matter of women’s literacy most of the study samples were illiterate (14.4%n=35) at the same time smallest group of them were at the post graduate level (2.2%, n=4). With regards to the residential area of the study participants a large number of them were came from urban residents (78.9%, n=142) on the other side, the lowest part of the enrolled samples were rural residents (6.1%, n=11). Concerning to the type of families of the recruited women in the study mostly were nuclear parents (80.6%, n=145) whereas small proportion of the participants were live with their in-laws (19.4%, n=35).Regarding the reasons for using the current method of contraception, most common reason for choosing was healthiness and safety (55.6%, n=100) least common chosen reason for using contraceptive methods was because it is cheap (22.2%, n=40). concerning to the common contraceptive method used in Qaladze district ,the majority were use coitous interruptus(51.7%), on the contrary injectable contraceptive and lactational amenorrhea method not used at all. Conclusion More than half of them in Qaladze chose healthiness and safety as a reason for using their current contraceptive method, while easiness in using a contraceptive method was the second most chosen reason for using their method, common contraceptive method used in the area was coitus interruptus which holds more than half of the participants, following by condom users, least methods used by them were lactational amenorrhea and injectable contraceptives